2011
DOI: 10.4084/mjhid.2011.028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Infection in the Pathogenesis of Vaso-Occlusive Crisis in Patients With Sickle Cell Disease.

Abstract: Sickle cell disease (SCD) is characterized by recurrent vaso-occlusive crisis (VOC). Patients with SCD have impaired immunity and are thus predispose to infections. The vast majority of SCD patients live in underdeveloped nations with high prevalence and transmission rates of infections. This makes the SCD patients prone to infections, which frequently precipitate VOC. We reviewed the role of infection in the pathogenesis of VOC, taking into consideration all potential mechanisms from previous studies and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 64 publications
(97 reference statements)
0
38
0
Order By: Relevance
“…Additionally, neutrophilia in SCA individuals can be accompanied by eosinopoenia. 7,8 Our findings showed that only one SCA patient presented with neutrophilia. Despite the significant difference (p = 0.045) observed in the eosinophil counts when the groups with and without the need for endodontic treatment were compared, eosinopoenia was not observed among the eligible patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Additionally, neutrophilia in SCA individuals can be accompanied by eosinopoenia. 7,8 Our findings showed that only one SCA patient presented with neutrophilia. Despite the significant difference (p = 0.045) observed in the eosinophil counts when the groups with and without the need for endodontic treatment were compared, eosinopoenia was not observed among the eligible patients.…”
Section: Discussionmentioning
confidence: 51%
“…Neutrophilia is a useful marker of infection in many clinical settings, as well as in SCA, 7,8 because the prevalence and intensity of neutrophilia are higher in SCA patients with bacterial infections than in those without infections. Additionally, neutrophilia in SCA individuals can be accompanied by eosinopoenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] It is therefore imperative that sickle cell disease patients with acute or chronic infections of the lungs must be closely monitored with blood gas analyzers so as to detect and correct hypoxia and its deleterious effect on red cell sickling. [14] …”
Section: Discussionmentioning
confidence: 99%
“…While (b) may explain the femoral and humeral head necrosis in this patient, haematogenous bacteria infection (c) appears to take prominence in this index patient in that severe abdominal crisis which the patient presented with among others could allow seepage of normal gut flora into the blood stream. Haematogenous spread is possible because SCD patients have sluggish circulation of blood in bones and also have compromised immune status attributable to many inherent factors such as defective microbial opsonization, tissue infarction and splenic hypofunction 11,12…”
Section: Discussionmentioning
confidence: 99%